Digital learning from home and the future of post-pandemic education - Achmad Hidayatullah; Muhammad Saud (PROCEEDING UMSURABAYA, 2020)
Abstract. This paper explains how the learning process from home is carried out during the pandemic era and how it will impact the future of education. The approach in this research is qualitative with the literature review method. But to strengthen the data, this study also uses interviews. In this pandemic era four obstacles were discovered, firstly the readiness of devices and networks, the cost of the internet network and the digital literacy capabilities of parents and teachers. In addition, learning done from home through online during the pandemic era had an impact on the future ofÂ  ducation in Indonesia. The learning experience in the pandemic era is increasingly a sign that it is not a single school or college that determines success. The decisive digital era is creativity and digital literacy, second, the class will be more flexible than ever which does not always require students to always come physically to school, and finally the stronger academic inflation, where degrees are no longer a sign of prestige.